Outcomes of Hemorrhage Control Training for Community Organizations in Rwanda - Longerstaey, Oriane; Denison, Kyle; Lee, Noelle; Nzeyimana, Innocent; Rutagumba, Dieudonne; Hughes, Ashley; Lacasse, Chelsea; Krebs, Elizabeth (Prehospital and disaster medicine, 2023)
Introduction:Traumatic injury from road traffic accidents is a major cause of morbidity and mortality in Rwanda. Basic first aid training can help bystanders to provide prehospital care. The objective of this study was to determine the impact of Stop the Bleed (STB) hemorrhage control training on participant knowledge, attitudes, and practices regarding bleeding control.Method:A total of 64 participants from two community organizations (Healthy People Rwanda and the Rwandan Emergency Care Association) were provided with training in STB. The course included a didactic presentation and skills session where participants could practice skills. A KAP (Knowledge, Attitudes, Practices) survey was provided to participants before training, immediately after training, three months, and six months post-training.Results:Immediately after training, participant knowledge of bleeding control techniques improved across 5 of 7 questions, including correct tourniquet placement (98% vs 85%) and the correct order of steps to take when treating bleeding (63% vs 9%). There was also a significant increase in confidence across six measures: identifying life-threatening bleeding, applying a tourniquet, applying direct pressure, wound packing, treating severe active bleeding, and teaching bleeding control techniques to others (p<0.001). After three months, 100% (n = 21) of participants reported using at least one skill from the course, and 95.24% (n = 20) reported using at least one piece of equipment provided during the course. After six months, 93.33% (28 of 30) of participants reported using at least one skill from the course, and 86.67% (26 of 30) reported using at least one piece of equipment provided during the course. Notably, 17 participants reported using the tourniquet they had received by six months post-training.Conclusion:This study found that STB training increased participant knowledge of bleeding control techniques and confidence in performing techniques for bleeding control. All participants reported using skills learned from the course.